Perlindungan Hukum Internasional atas Pelanggaran HAM terhadap Suku Papua dalam Kaum Indegenous di Indonesia - Rifki Aditya; adillah Melani Putri; Reh Bungana Beru Perangin-Angin (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to find out how international legal regulations deal with human rights against indigenous Papuans. Human Rights (HAM) in general can be interpreted as the basic rights that a person has because of his human status. Human rights are universal. In essence, all categories of human rights are universal, interdependent and interrelated. The state has the full obligation to protect the human rights of every individual, such as protection from abuse of state power and authority, protection from torture by those in power, therefore the state must fulfill its authority in defending and upholding its existence. regarding the protection of human rights. The research method used in this research is library research. In addition, in the process of making this article, the type of research used in this research is normative. However, in reality, human rights regulations and law enforcement in Papua itself are not running according to the expectations of the tribal people of the interior of Papua because of obstacles in enforcing civil society.